Quality of Life in Patients with Rheumatoid Arthritis: Relation with Disease Activity, Functional and Health Status - Taciser Kaya; Altınay Göksel Karatepe; Rezzan Günaydın; Gül Türkmen; Gülriz Özbek (Archives of Rheumatology, 2007)
Objective: To investigate the effects of disease activity, functional capacity and several dimensions of health status on the level of quality of life in patients with rheumatoid arthritis. Patients and Methods: Thirty-two patients (F/M=30/2) who fulfilled the American College of Rheumatology diagnostic criteria for rheumatoid arthritis were included in this study. Demographic characteristics of patients were recorded. Functional status, health status and quality of life were respectively measured by using Health Assessment Questionnaire (HAQ), Arthritis Impact Measurement Scale2 (AIMS2) and Rheumatoid Arthritis Quality of Life (RAQoL). Results: The mean of ages and disease duration were 51.0±11.8 (28-70) and 11.8±10.0 (1-40) years. There was a statistically significant relation between RAQoL and HAQ (r= 0.472, p= 0.008), mobility (r= 0.379, p= 0.039), walking (r= 0.515, p= 0.004), self care (r= 0.640, p<0.001) and household tasks (r= 0.640, p<0.001) subscales of AIMS2. HAQ correlated with mobility, self care and household tasks and pain subscales of AIMS2 (respectively r= -0.364, -0.559, 0.456, -0.671; p= 0.040, 0.001, 0.009, 0.001). The most important determinants of quality of life were determined as HAQ and walking subscale of AIMS2 (respectively β= 4.013, 1.041 p= 0.021, 0.031). Conclusion: It was shown that rather than disease activity, functional and health status were associated with quality of life. According to our data, amelioration of functional status must be the essential target while controlling pain and disease activity in the treatment of rheumatoid arthritis. (Rheumatism 2007; 22: 119-22)